Modelling the Relationships between Coping Styles, Illness Perception, Perceived Social Support, and Psychological Resilience in Patients with Chronic Migraine - Kordmirza Nikoozadeh, Ezzatollah; Karfeh Raveshi, Fatemeh; Moghimi, Saranaz; Rafiepoor, Amin (Psychology of Woman Journal, 2025)
Objective: This study aimed to model the relationships between coping styles, illness perception, perceived social support, and psychological resilience in women diagnosed with chronic migraine.Methods and Materials: A correlational descriptive design was employed with a sample of 400 women aged 18–60 years, all medically diagnosed with chronic migraine and residing in Tehran. Participants were selected using convenience sampling, and data were collected using validated self-report instruments: the Connor-Davidson Resilience Scale (CD-RISC), Coping Inventory for Stressful Situations (CISS), Illness Perception Questionnaire-Revised (IPQ-R), and Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using SPSS version 27. Descriptive statistics, Pearson correlation coefficients, and multiple linear regression analysis were conducted to explore associations and predictive relationships among the variables.Findings: Descriptive statistics showed moderate to high levels of psychological resilience and perceived social support among participants. Pearson correlation analysis revealed that psychological resilience was positively correlated with task-oriented coping (r = .61, p < .001) and perceived social support (r = .66, p < .001), and negatively correlated with emotion-oriented coping (r = −.42, p < .001), avoidance-oriented coping (r = −.18, p = .003), and negative illness perception (r = −.55, p < .001). The multiple regression model including all five predictors was significant, F(5, 394) = 178.98, p < .001, explaining 70.2% of the variance in psychological resilience. Perceived social support (β = .44) and task-oriented coping (β = .32) were the strongest positive predictors, while illness perception (β = −.29), emotion-oriented coping (β = −.19), and avoidance-oriented coping (β = −.09) were significant negative predictors.Conclusion: The findings underscore the importance of adaptive coping strategies, positive illness beliefs, and strong social support in enhancing psychological resilience among women with chronic migraine. Interventions targeting these psychosocial factors may improve patients’ adaptive capacity and overall well-being.